Local Applications of Myostatin-siRNA with Atelocollagen Increase Skeletal Muscle Mass and Recovery of Muscle Function - Kawakami, Emi (Public Library of Science, 2013)
BACKGROUND: Growing evidence suggests that small-interfering RNA (siRNA) can promote gene silencing in mammalian cells without induction of interferon synthesis or nonspecific gene suppression. Recently, a number of highly specific siRNAs targeted against disease-causing or disease-promoting genes have been developed. In this study, we evaluate the effectiveness of atelocollagen (ATCOL)-mediated application of siRNA targeting myostatin (Mst), a negative regulator of skeletal muscle growth, into skeletal muscles of muscular dystrophy model mice. METHODS AND FINDINGS: We injected a nanoparticle complex containing myostatin-siRNA and ATCOL (Mst-siRNA/ATCOL) into the masseter muscles of mutant caveolin-3 transgenic (mCAV-3Tg) mice, an animal model for muscular dystrophy. Scrambled (scr) -siRNA/ATCOL complex was injected into the contralateral muscles as a control. Two weeks after injection, the masseter muscles were dissected for histometric analyses. To investigate changes in masseter muscle activity by local administration of Mst-siRNA/ATCOL complex, mouse masseter electromyography (EMG) was measured throughout the experimental period via telemetry. After local application of the Mst-siRNA/ATCOL complex, masseter muscles were enlarged, while no significant change was observed on the contralateral side. Histological analysis showed that myofibrils of masseter muscles treated with the Mst-siRNA/ATCOL complex were significantly larger than those of the control side. Real-time PCR analysis revealed a significant downregulation of Mst expression in the treated masseters of mCAV-3Tg mice. In addition, expression of myogenic transcription factors was upregulated in the Mst-siRNA-treated masseter muscle, while expression of adipogenic transcription factors was significantly downregulated. EMG results indicate that masseter muscle activity in mCAV-3Tg mice was increased by local administration of the Mst-siRNA/ATCOL complex. CONCLUSION: These data suggest local administration of Mst-siRNA/ATCOL complex could lead to skeletal muscle hypertrophy and recovery of motor disability in mCAV-3Tg mice. Therefore, ATCOL-mediated application of siRNA is a potential tool for therapeutic use in muscular atrophy diseases.